Exploring Meaning and Types of Trust in Maternity Care in Peri-Urban Kenya: A Qualitative Cross-Perspective Analysis. (January 2018) - Sripad, Pooja; Ozawa, Sachiko; Merritt, Maria W.; Jennings, Larissa; Kerrigan, Deanna; Ndwiga, Charity; Abuya, Timothy; Warren, Charlotte E.
Trust offers a distinctive lens on facility responsiveness during labor and birth. Though acknowledged in prior literature, limited work exists linking conceptual and empirical spheres. This study explores trust in the maternity setting in Kenya through a theoretically driven qualitative approach. Focus groups ( n = 8, N = 70) with women who recently gave birth (WRB), pregnant women, and male partners, and in-depth-interviews ( n = 33) with WRB, frontline providers, and management, were conducted in and around a peri-urban public hospital. Combined coding and memo-writing showed that trust in maternity care is nested within understandings of institutional and societal trust. Content areas of trust include confidence, communication, integrity, mutual respect, competence, fairness, confidentiality, and systems trust. Trust is relevant, multidimensional, and dynamic. Examining trust provides a basis for developing quantitative measures and reveals structural underpinnings, repercussions for trust in other health areas, and health systems inequities, which have implications for maternal health policy, programming, and service utilization.